The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1155/2013/979185
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Associations of Depressive Symptoms with Cardiovascular Risk Factors and Metabolic Syndrome among African Americans

Abstract: Young to middle-aged women usually have notably lower rates of cardiovascular disease (CVD) than their male counterparts, but African American women lack this advantage. Their elevated CVD may be influenced by sex differences in associations between depressed mood and CVD risk factors. This cross-sectional study examined whether relations between scores on the Center for Epidemiologic Studies-Depression (CES-D) scale and a spectrum of CVD risk factors varied by sex among African Americans (n = 1076; ages 30–64… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 51 publications
3
20
2
Order By: Relevance
“…The study conducted by Cooper et al among African Americans showed that the greater the abdominal obesity, the more intensive depressive symptoms are. 76 Our study confirmed a positive correlation between WC and the BDI.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The study conducted by Cooper et al among African Americans showed that the greater the abdominal obesity, the more intensive depressive symptoms are. 76 Our study confirmed a positive correlation between WC and the BDI.…”
Section: Discussionsupporting
confidence: 82%
“…18,[72][73][74][75][76] The EZOP Poland study showed that women more often show symptoms of depression. 67 The present study confirmed this dependence.…”
Section: Discussionmentioning
confidence: 99%
“…[4,7,8] A significant positive association between the Centre for Epidemiologic Studies Depression Scale (CES-D) and hsCRP levels among African-American men with depression was found that was absent in their female counterparts. [13] However, no such gender based variations regarding the association of hsCRP with depression was observed in the present study.…”
Section: Discussioncontrasting
confidence: 67%
“…Evidence has suggested, however, that alcohol consumption is associated with early risk markers of cardiometabolic diseases, such as IR and fasting insulin, in a sex-specific manner [10, 36, 37]. It has been suggested that sex differences in the relationship between alcohol intake and metabolic markers are explained by adiposity [12].…”
Section: Resultsmentioning
confidence: 99%